Self-Concept Images In Female Students Who Use Harmful Cosmetic Products - Subrata, Shinta Maylinda; Paryontri, Ramon Ananda (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Many cosmetics are not matched by a knowledge by consumers. The cosmetics in the public warning attachment consist of 37 cosmetics that are not notified and 31 have notification numbers that have been canceled. These hazardous materials have actually been prohibited from being added to cosmetics since 1998 with the issuance of Regulation of the Minister of Health of the Republic of Indonesia No. 445/Menkes/Per/V/1998 . This fact was proven by female students at the Muhammadiyah University of Sidoarjo with the results of interviews with female students from different study programs regarding their respective opinions regarding self-concept of using cosmetics containing hazardous ingredients. The purpose of this research is to find out the self-concept description of female students who use dangerous cosmetic products. This research method uses qualitative methods. The units of analysis in this study are (1) female students; (2) Self-Concept. The subjects and settings of this research were the subjects of students from several study programs and research locations at the Muhammadiyah University of Sidoarjo. Data collection techniques using observation, interviews, and documentation. The validity of the data using Method Triangulation and Theory Triangulation. Researchers use data analysis techniques according to Miles and Huberman in 3 stages, namely: (1) Data reduction; (2) Data presentation; (3) Drawing conclusions or verification. The results of the study of four female student subjects from the Muhammadiyah University of Sidoarjo had their own influence to continue using and continuing to use this dangerous cosmetic. Among them, S1 influence on peers, Masters influence on social media, Masters influence with admired idols or foreign artists, and Masters due to parents' demands. Research findings from interviews: dangerous cosmetic buying behavior, improving appearance, need to be praised, need to be appreciated, need to be sued by parents, high self-monitoring, low self-perception, anxiety, low self-principleBanyak kosmetik yang tidak diimbangi oleh suatu pengetahuan konsumen. Kosmetik dalam lampiran public warning tersebut terdiri dari 37 kosmetik tidak ter notifikasi dan 31 memiliki nomor notifikasi yang telah dibatalkan.Bahan berbahaya tersebut sebenarnya dilarang untuk ditambahkan pada kosmetik sejak tahun 1998 dengan dikeluarkannya Peraturan Menteri Kesehatan RI No. 445/Menkes/Per/V/1998 .Fakta inidibuktikan pada mahasiswi Universitas Muhammadiyah Sidoarjo dengan hasil wawancara pada mahasiswi dari program studi yang berbeda tentang pendapat masing-masing mengenai konsep diri memakai kosmetik mengandung bahan berbahaya.Tujuan penelitian untuk mengetahui gambaran konsep diri pada mahasiswi yang menggunakan produk kosmetik yang berbahaya. Metode penelitian ini menggunakan metode kualitatif. Subjeknya yaitu subjek dari mahasiswa dari beberapa program studi. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Keabsahan data menggunakan Triangulasi Metode dan Triangulasi Teori. Peneliti menggunakan teknik analisis data menurut Miles dan Huberman dalam ada 3 tahapan yaitu: (1)Reduksi Data;(2)Penyajian Data;(3) Penarikan Kesimpulan atau Verifikasi. Penelitian ini menemukan bahwa penggunaan kosmetik berbahaya dipengaruhi oleh faktor seperti pengaruh teman sebaya, media sosial, idola/artis luar negeri, dan tuntutan orang tua. Temuan penelitian juga menunjukkan bahwa penggunaan kosmetik berbahaya terkait dengan upaya memperbaiki penampilan, kebutuhan akan pujian dan penghargaan, serta tingkat pemantauan diri yang tinggi. Subjek penelitian juga memiliki persepsi diri rendah, mengalami kecemasan, dan memiliki prinsip diri yang rendah.